A strategy for the treatment of gastrointestinal cancer: Targeting tumor senescent cells - Liu, Yujing; Zhang, Qiang; Ni, Wenjing; Ji, Guang; Xu, Hanchen (Frontiers in Molecular Biosciences, 2023)
Gastrointestinal (GI) cancer includes a variety of cancers with high incidence that seriously threaten the lives of people worldwide. Although treatment strategies continue to improve, patient benefits are still very limited, and the ongoing search for new treatment strategies remains a priority. Cell senescence is closely related to the occurrence and development of tumors. For GI cancer, cell senescence may not only promote cancer but also bring new opportunities for treatment. Combined with relevant studies, we review the dual role of cell senescence in GI cancer, including the mechanism of inducing cell senescence, biomarkers of senescent cells, and potential of targeted senescence therapy for GI cancer.